Comparative transcriptomic analyzes of human lung epithelial cells infected with wild-type SARS-CoV-2 and its variant with a 12-bp missing in the E gene - Sun, Yi-Sheng; Sun, Hao; Zhu, Han-Ping; Li, Gao-Lei; Xu, Fang; Lu, Hang-Jing; Tang, An; Wu, Bei-Bei; Li, Yu-Dong; Yao, Ping-Ping; Jiang, Jian-Min (Frontiers in Microbiology, 2023)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel coronavirus that causes a global outbreak of coronavirus disease 2019 (COVID-19) pandemic. To elucidate the mechanism of SARS-CoV-2 replication and immunogenicity, we performed a comparative transcriptome profile of mRNA and long non-coding RNAs (lncRNAs) in human lung epithelial cells infected with SARS-CoV-2 wild strain (8X) and the variant with a 12-bp deletion in the E gene (F8). In total, 3966 differentially expressed genes (DEGs) and 110 differentially expressed lncRNAs (DE-lncRNAs) candidates were identified. Of which, 94 DEGs and 32 DE-lncRNAs were found between samples infected with F8 and 8X. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that pathways such as TNF signaling pathway and viral protein interaction with cytokine and cytokine receptor were involved. Furthermore, we constructed a lncRNA-protein-coding gene co-expression interaction network. The KEGG analysis of the co-expressed genes showed that these differentially expressed lncRNAs were enriched in pathways related to immune response, which might be the reason for the different replication and immunogenicity of the 8X and F8 strains. These results provided a useful resource for studying the pathogenesis of SARS-CoV-2 variants.